2014
DOI: 10.3354/aei00091
|View full text |Cite
|
Sign up to set email alerts
|

Nematode assemblage response to fish-farm impact in vegetated (Posidonia oceanica) and non‑vegetated habitats

Abstract: We investigated the impact of fish farming on the benthic biota of 2 habitats (seagrass meadows of Posidonia oceanica and non-vegetated soft bottoms), by examining in detail the nematode assemblages, and the effects of organic enrichment on their abundance, diversity (species richness and trophic diversity), community structure and individual size. All investigated faunal variables differed significantly between impact and control sediments, except for individual nematode biomass. Nematodes displayed reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Other studies found that the analysis of nematode assemblages at the genus level represents the most informative tool in relation to the EcoQ: in the study of Losi et al (2013a) the analysis of the nematode assemblage at the level of genus revealed the best connection between environmental status and biological response, and in Losi et al (2012) only the genera analysis brought to light early changes in the community due to the touristic pressure. The same results are reported by Vezzulli et al (2008) and Mirto et al (2014) in relation to the fish farm impact and by Schratzberger et al (2009) in relation to physical stress.…”
Section: Taxonomic Structuresupporting
confidence: 76%
See 3 more Smart Citations
“…Other studies found that the analysis of nematode assemblages at the genus level represents the most informative tool in relation to the EcoQ: in the study of Losi et al (2013a) the analysis of the nematode assemblage at the level of genus revealed the best connection between environmental status and biological response, and in Losi et al (2012) only the genera analysis brought to light early changes in the community due to the touristic pressure. The same results are reported by Vezzulli et al (2008) and Mirto et al (2014) in relation to the fish farm impact and by Schratzberger et al (2009) in relation to physical stress.…”
Section: Taxonomic Structuresupporting
confidence: 76%
“…In a good portion of the reported study cases, MI responded to the stressors, proving to have the potential as quality status indicator (Mirto et al, 2002(Mirto et al, , 2014Semprucci et al 2010aSemprucci et al , 2013a. In agreement with those results, Moreno et al (2011), evaluating several nematode indices for EcoQ assessment, found that c-p composition and MI were among the best tools to evaluate the EcoQ.…”
Section: Maturity Indexsupporting
confidence: 68%
See 2 more Smart Citations
“…Current instruments that can analyze chlorophyll-a from in situ sampling can ground-truth satellite image analysis for monitoring of phyto-pigments concentrations in surface waters (Cristina et al, 2014(Cristina et al, , 2016 or assess aquaculture impacts (Mirto et al, 2010(Mirto et al, , 2014Luna et al, 2013;Bengil and Bizsel, 2014). In addition, pigment color analysis (particularly in situ flow cytometry) can provide insights on phytoplankton biodiversity , estimate and calculate time series of annual gross primary production, and support MSFD implementation .…”
Section: Descriptor 5 (Eutrophication)mentioning
confidence: 99%